Energi Surya Sebagai Solusi Dalam Peningkatan Efisiensi Energi Perspektif SDGs 7 (Sustainable Development Goals 7 ) 2030: (Studi Kasus Penerapan Panel Surya Mewujudkan Smart And Green Campus di UNTIRTA) - Shafa Yuniar Yasmin; Feri Febrian Syah; M. Ashof Azria Azka; Didik Aribowo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Sustainable Development Goals (SDGs) are a global action plan agreed upon by world leaders, including Indonesia, to achieve sustainable development in all aspects, especially in the use of renewable energy sources. For Indonesia, the implementation of SDGs can contribute to the country's progress and development, especially in the use of solar energy as an alternative energy source. Solar energy consistently dominates the expansion of renewable energy capacity, making it the main focus of sustainable development efforts in Indonesia. In fact, solar energy accounted for 73% of renewable energy growth last year, reaching a capacity of 1,419 GW, followed by wind energy with a 24% share in renewable energy expansion. The emphasis on solar power and other renewable energy sources is in line with Indonesia's goal of becoming a fully developed country. The research method used in this scientific article is the literature study method. A literature review that focuses on a particular topic to identify a theory or method, develop the theory or method, and summarize its development. Therefore, the aim of this paper is to reveal that the role of solar energy in increasing energy efficiency is very important and is growing very significantly every year.